The Ghosts of Old Volcanoes, a Geoheritage Trail Concept for Eastern Coromandel Peninsula, New Zealand - Ilmars Gravis; Karoly Nemeth; Chris Twemlow; Boglarka Nemeth (Geoconservation Research)
Re-imagining the geotourism experience through the lens of slow tourism, in this paper we lay out a pathway towards a more nourishing, engaging, and educational experience that contributes to both geoconservation and a reshaping of the tourism economy in light of recent disruption caused by the Covid-19 pandemic. Evidence suggests that to date, and further highlighted by unfolding local and global responses to the pandemic, mainstream approaches to conservation, protection, and tourism have poorly served our unique geoheritage landscapes and features. We demonstrate the potential for community led development utilising internationally recognized practices to provide a foundation for low impact and sustainable tourism, education, and training opportunities of benefit to local, regional, and national communities. We identify the eastern Coromandel, including Kuaotunu Peninsula, as an area for potential research and identification of sites with high geological, environmental, and cultural values. A geotrail has the potential to tell the story of formation of rhyolitic caldera walls enclosing translucent azure waters framed by white silica sands. Cultural sites are a landscape record giving voice to indigenous Māori that began the human story of adapting to and modifying the landscape. Our premise is that a geotrail offers a more sophisticated experience by weaving together conservation stories, science communication, indigenous history, and local lore. Our goal is to develop a physical and virtual geotrail, complemented by learning and promotional media highlighting the layers of natural and human history, building on a foundation of already published scientific, social, and historical research. Global disruption caused by the current pandemic gives us cause to reflect and consider management of a growing tourism footprint and economic reliance on singular landscapes. We recognize this as an opportunity to reassess a tourism model based on a high-volume of short stay visits to iconic sites.